2018
DOI: 10.1093/ofid/ofy210.434
|View full text |Cite
|
Sign up to set email alerts
|

423. Ten-Year Experience of Burkholderia pseudomallei Infections in a Singapore Tertiary Hospital

Abstract: Background Burkholderia pseudomallei is endemic in the tropics and associated with high mortality. We performed a retrospective study analyzing the clinical and microbiologic features of melioidosis, and predictors of mortality.MethodsPatients with culture-positive melioidosis from 2006 to 2016 were identified from microbiologic records. Clinical data including demographics, treatment, and outcomes were extracted from medical records. Categorical variables were compared using χ2 test or Fisher exact test while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is also much lower than in other endemic regions such as Thailand (35%) [26] and India (17%) [18]. A Singaporean tertiary hospital reported a melioidosis mortality rate of 20.9% and the time from admission to initiation of antibiotics to be 6.8 AE 9.1 days [27]. Other areas in Malaysia, such as Johor, Perak and Pahang, reported that only 15.6%, 28.9% and 51.9% of melioidosis patients were given appropriate antibiotics, respectively [16,25,28].…”
Section: Discussionmentioning
confidence: 90%
“…It is also much lower than in other endemic regions such as Thailand (35%) [26] and India (17%) [18]. A Singaporean tertiary hospital reported a melioidosis mortality rate of 20.9% and the time from admission to initiation of antibiotics to be 6.8 AE 9.1 days [27]. Other areas in Malaysia, such as Johor, Perak and Pahang, reported that only 15.6%, 28.9% and 51.9% of melioidosis patients were given appropriate antibiotics, respectively [16,25,28].…”
Section: Discussionmentioning
confidence: 90%